Effect of a daily outdoor access on the urination and defecation behaviors and nitrogen excretion by lactating cows - Bailoni, Lucia; Arango, Sheyla; Guzzo, Nadia; Currò, Sarah; Bianco, Emanuele; Simonetti, Emilio; Zerbinati, Elena; Rainis, Simona; Sartori, Cristina (Frontiers in Veterinary Science, 2025)
This study aimed to assess the urination and defecation frequency along with the nitrogen excretion produced by lactating cows spending either 2 or 4 h a day in an outdoor exercise area, to then estimate the load of cows allowed considering the nitrogen limitation in manure established by the EU directive. Six Italian Simmental lactating cows housed in a free-stall were paired and alternatively subjected to the following exit managements: no daily outdoor access, a 2-h daily outdoor access (U2; from 11:30 a.m. to 1:30 p.m.), and a 4-h daily outdoor access (U4) divided into a morning (U4a; 9:00 to 11:00 a.m.) and an afternoon (U4b; 2:00 to 4:00 p.m.) exit. Using a crossover design, each pair of cows was subjected to each exit management for a period of 2 weeks, then switched twice, until the completion of 6 weeks of evaluation in order to ensure all the three different group combinations. The study considered as treatments the two exit managements: U2 and U4. Cows in the paddock urinated and defecated on average 0.76 and 0.94 times per hour, respectively. The content of nitrogen in urine and feces was 0.42% and 1.96% on average, respectively. Excretion variables such as nitrogen output of urine, nitrogen output of feces and total nitrogen output were 6.19, 4.91, and 11.10 g/h on average respectively, and they were not affected by the treatment. The total nitrogen output by the cows spending 2 or 4 h of daily outdoor activity was 22.68 and 44.07 g per cow, respectively (P < 0.001). In conclusion, the duration of the outdoor exit did not influence the number of urination or defecations events per hour, the nitrogen excretion output in urine and feces, and therefore, the total nitrogen output per hour in the outside paddock. Considering a 2 or 4-h daily exit along the whole year and the limit of nitrogen of 170 kg N/ha/year given by the EU Directive, the maximum stocking rate per hectare would be equal to 21 and 11 dairy cows, respectively.